Some Questions Raised by the Targeted Killing of General Soleimani - Fornari, Mateo (2020)
The targeted killing of Iranian general, Qasem Soleimani, on 3 January 2020 by a drone strike by the United States, raises some international law issues. With regard to the law of armed conflict, it may be asked whether this action is part of an existing armed conflict; if there was no armed conflict between the United States and Iran prior to the assassination of Soleimani, the question then arises as to whether this same action, in itself, has led to the beginning of an armed conflict between the two countries. Established that the United States and Iran would not be acting within the framework of the jus in bello, the assassination of Soleimani can be assessed in the context of the right to use force, that is, the jus ad bellum.  In this context, the interpretation and application of the right of self-defence invoked by the United States raises doubts.